2020
DOI: 10.1186/s12891-020-03241-1
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variation of the Psoas Valley: a scoping review

Abstract: Background: This scoping review aimed to investigate the literature on the anatomy of the psoas valley, an anterior depression on the acetabular rim, and propose a unified definition of the anatomical structure, describe its dimensions, anatomical variations and clinical implications. Methods: A systematic computer search of EMBASE, PubMed and Cochrane for literature related to the psoas valley was undertaken using Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Clinical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Similarly, PMI was more strongly associated with FRAX (major osteoporotic and hip fractures) than SMI, which partly means that PMI is a better predictor of osteoporosis and hip fractures over the next decade than SMI. Compared with skeletal muscle and adipose tissue at the same level, the L3 level of abdominal CT can better show the position and area of the psoas muscle [ 21 , 22 ]. This indicates that PMI at the L3 level can better reflect the muscle mass of the whole body, which to some extent, explains the result of this study that PMI has better predictive ability than SMI, SFI, VFI, and VSR.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PMI was more strongly associated with FRAX (major osteoporotic and hip fractures) than SMI, which partly means that PMI is a better predictor of osteoporosis and hip fractures over the next decade than SMI. Compared with skeletal muscle and adipose tissue at the same level, the L3 level of abdominal CT can better show the position and area of the psoas muscle [ 21 , 22 ]. This indicates that PMI at the L3 level can better reflect the muscle mass of the whole body, which to some extent, explains the result of this study that PMI has better predictive ability than SMI, SFI, VFI, and VSR.…”
Section: Discussionmentioning
confidence: 99%
“…The most effective location for iliopsoas tenotomy remains uncertain, with particular concerns noted regarding the risk of post-operative weakness. Previous MRI studies have demonstrated both higher rates and greater degrees of iliacus atrophy when tenotomy is performed at the level of the lesser trochanter when compared to the labrum [7,16,19]. These studies also reported a 25% rate of gluteus maximus atrophy and 35% rate of chronic iliopsoas tendon disruption in post-operative MRI when the tenotomy was performed at the lesser trochanter.…”
Section: Discussionmentioning
confidence: 90%
“…The role of multiple iliopsoas tendon in ISHS remains an area of debate [16,17]. A study using dynamic sonography in 18 snapping hips suggested that this pathology could be due to the trapping of the iliopsoas tendon on the anterior surface of the iliacus muscle body and its abrupt collision with the pubic bone upon lateral release [1,4,6].…”
Section: Discussionmentioning
confidence: 99%
“…The measurement at the AIIS position, corresponding to the AIIS where ‘psoas valley’ starts [ 22 ], showed that AIIS medially houses a major depression in continuity with the so-called ‘psoas tunnel’ [ 11 ] ( Fig. 3 ).…”
Section: Discussionmentioning
confidence: 99%